Aural Full and Otogenic Pain Redux. (2nd September 2014) - Micco, Alan G.; Megerian, Cliff A.; Toh, Elizabeth H.; Angeli, Simon I.
Abstract : Program Description: Otogenic pain and aural fullness can be some of the more frustrating chief complaints to work up and address. Many patients with this complaint are frustrated with lack of diagnosis and treatment. This leads to multiple visits in search of the answer to their affliction. In this miniseminar, our panel of experts will continue their discussion on how to evaluate and treat these difficult patients. Paradigms for management of these patients will be discussed. Case presentations will highlight proper workup and management of these confusing cases. Sponsored by the Otology and Neurotology Education Committee. Educational Objectives: (1) Describe pathologies that may cause otogenic pain or aural fullness. (2) Conduct workup paradigms to avoid missing potentially dangerous processes. (3) Examine possible treatments for the various pathologies.